2022
DOI: 10.1177/15589447221081564
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Radiologic and Functional Outcome of Radial Shortening Versus Capitate Shortening in Management of Kienböck’s Disease

Abstract: Background: Kienböck’s disease is the avascular necrosis of the lunate bone. There is no consensus on the treatment strategy to avoid joint deterioration. This trial is conducted to compare the functional and radiological outcomes of radial shortening and capitate shortening techniques, in patients with avascular necrosis of lunate. Methods: Patients with a confirmed diagnosis of Kienböck’s disease who met the inclusion criteria were randomly divided into radial shortening and capitate shortening groups and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…In a biomechanical study, Kam et al 41 showed a very similar reduction in lunate cortical strain in both radial opening wedge and closing wedge osteotomies. While others prefer capitate shortening, 42,43 there are biomechanical studies that report a risk of overloading the midcarpal joint. 37 Our preference is for a closing wedge osteotomy as it lessens the risk of nonunion associated with an opening wedge osteotomy and avoids the risk of midcarpal overload from capitate shortening.…”
Section: Intact Lunate Cortex On Computed Tomography Scanmentioning
confidence: 99%
“…In a biomechanical study, Kam et al 41 showed a very similar reduction in lunate cortical strain in both radial opening wedge and closing wedge osteotomies. While others prefer capitate shortening, 42,43 there are biomechanical studies that report a risk of overloading the midcarpal joint. 37 Our preference is for a closing wedge osteotomy as it lessens the risk of nonunion associated with an opening wedge osteotomy and avoids the risk of midcarpal overload from capitate shortening.…”
Section: Intact Lunate Cortex On Computed Tomography Scanmentioning
confidence: 99%
“…Partial shortening of the large bone is a decompression technique for the treatment of lunatomalacia with positive or neutral ulnar variance. The large bone shortening technique done by means of a smaller cut takes less time compared to radial shortening and leads to an advantage in stage II (15,16).…”
Section: Figure 3 Degree Of Carpal Collapse By Salmon Et Al Through T...mentioning
confidence: 99%